Molecular Identification of Microsporum canis Isolated from Infected Children with Tinea corporis and Tinea capitis in Baghdad - Hamied, Atyaf Saied; Alnedawy, Qusay (Iraqi Journal of Science, 2024)
Microsporum canis is considered one of the filamentous fungi that cause surface fungal contagion in the humans and animals. The present study aimed to diagnose M. canis via the molecular method and differentiating its local Iraqi isolates from global isolates. Microscopic examination showed 55 specimens with M. canis from 130 specimens collected from children aged between 4-10 years suspected of dermatophytes who attended Medical City Laboratories and Baghdad Hospital in Baghdad city from 1/12/2022 to 1/3/2023. The results showed that the frequency of M. canis infections was 55/130 (42.31%). The results demonstrated significant differences in the animals' contact (p <0.0001), lesions (0.03) and habitation area (p =0.002). Whilst the ages appeared with non-significant differences (p =0.6). In order to confirm the microscopic examination and compare the Iraqi isolates with other global ones, the 55 positive results with M. canis were further diagnosed by using internal transcribed spacer (ITS) 1 and 4 universal primers with a size of 550 bp for PCR amplicons. PCR amplicons sequencing showed only one isolate of M. Canis that differed from global isolates registered in the database of NCBI. The Iraqi local isolate of M. canis was registered with accession number: OM185328. In conclusion, the PCR technique using ITS rDNA aided in confirming the detection of dermatophytes.